A ternary composite oxides S2O82−/ZrO2–TiO2–SiO2 as an efficient solid super acid catalyst for depolymerization of lignin. Issue 79 (26th October 2017) - Wang, Huizhen; Li, Wenzhi; Wang, Jindong; Chang, Hou-min; Jameel, Hasan; Zhang, Qi; Li, Song; Jin, Lele
Abstract : The solid, super, acid catalyst S2 O8 2− /ZrO2 –TiO2 –SiO2, which has both a strong Brønsted acid and Lewis acid, was prepared and applied in lignin depolymerization. Abstract : The solid, super, acid catalyst S2 O8 2− /ZrO2 –TiO2 –SiO2, which has both a strong Brønsted acid and Lewis acid, was prepared and applied in lignin depolymerization. The results indicate that S2 O8 2− /ZrO2 –TiO2 –SiO2 is an effective catalyst for lignin depolymerisation since the liquid product was almost completely dissolved in ethyl acetate, indicating that it was comprised of mostly oligomeric lignin degradation products. The effect of hydrogenation co-catalysts (Pd/C, Pt/C and Ru/C, Rh/C) were also studied and found to improve the yield of aromatic compounds and the petroleum ether soluble fraction, which are mostly monomeric and dimeric products. The resulting yields of aromatic compounds and petroleum ether soluble products were 14.8% and 46%, respectively, when S2 O8 2− /ZrO2 –TiO2 –SiO2 and Pt/C mixed catalyst was used at 310 °C for 24 hours. These results show that the use of a combination Brønsted and Lewis acid catalyst in combination with a hydrogenation catalyst (S2 O8 2− /ZrO2 –TiO2 –SiO2 together with a noble metal catalyst) opens a practical route for efficient lignin depolymerization.